Determine the Association of Thymus and Activation-regulated Chemokine (TARC)/CCL17 with Asthma Severity. - Duaa Almyali; Rana Fadhil Obaid (مجلة الكوفة الطبية, 2025)
Background: Asthma is a long-term respiratory disease that results in signs including coughing, chest tightness, wheezing, and shortness of breath due to inflammation and airway narrowing. Th2 cells, a subtype of T helper cells, are particularly attracted to the inflammatory region by novel asthma biomarkers, consisting of thymus and activation-regulated chemokine (TARC)/CCL17, which functions as an indicator of the severity of illnesses and the treatment's efficacy. Objective: This study assesses the association between serum concentration of (TARC)/CCL17 and asthma severity in adult patients. Patients and methods: Respiratory physicians diagnose Asthmatic patients based on the Global Initiative for Asthmatic Patients (GINA)guideline. Classified patients with asthma, according to GINA guidelines, the asthma control test (ACT), and serum biomarkers (TARC) are evaluated using an ELISA kit. Of the 140 participants, ranging in age from 18 to there were 70 cases and 70 controls in this case-control study were matched in age, and six to six cases. Result:  Higher serum levels of TARC in the case, but no statistically significant p-values (0.528). Considering the correlation between study indicators' serum levels along with ACT, GINA, and duration, p-value>0.05, these differences were not statistically significant. Patients with a family history of asthma appeared to be significant in asthmatic individuals. Conclusion: There are differences between the patients and control groups, but no significant apparent differences. Significant variations were not found in correlation with GINA, ACT, or asthma duration, while significant with family history, indicating the biomarker is not correlated with the severity and control of asthma.